Performance Evaluation of Motorcycle Racing Cast Wheels Under Dynamic Load Using Finite Element Method with Aluminum Material - Agus Dwi Putra; Diama Rizky Septiawan; Yayi Febdia Pradani; Nicko Nur Rakhmaddian; Muhammad Arif Nur Huda (Universitas Islam Raden Rahmat, Malang, 2025)
The racing cast wheel made of aluminum 6061-T6 is a critical component in motor vehicles, particularly in supporting performance, safety, and aesthetics. This study aims to analyze the mechanical performance of the wheel through Finite Element Analysis (FEA) simulation. The FEA simulation was conducted using Ansys 18.1 software with a load of 1500 N, covering both static and dynamic loading conditions. The material tested is Aluminum Alloy 6061-T6, with material properties derived from tensile testing. The simulation results indicate that maximum stress occurs in critical areas, such as bolt holes and the intersection of spokes with the wheel rim, with a maximum stress value of 46.027 MPa. This stress level remains below the material's yield strength (276 MPa), demonstrating that the design is safe from plastic deformation. The total deformation observed is 0.053 mm, which is negligible and does not affect the wheel's functionality. A safety factor exceeding 2.5 confirms that the wheel can withstand more extreme loads. Based on these findings, design optimizations such as adding fillets and surface treatments are recommended to enhance the wheel's reliability. This research provides valuable insights for the development of stronger, lighter, and more durable wheels, particularly suited to the diverse road conditions found in Indonesia.